(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
Interpretation of an amazing combination of a sharp weapon and blunt force impact injury on the neck created an understanding that the victim had been injured. Observation of the crime scene by forensic medicine experts 13 days after the death and subsequent correlation with autopsy findings revealed that the bleeding was from the accidental cut sustained while cutting the noose. This case is reported for its rarity, for the awareness of the possible post-mortem bleeding artefact, to explain the circumstances of such a possibility, and to emphasize the importance of involving forensic medicine experts as a part of the crime scene investigation team. A deceptive presentation of suicidal death by “hanging” should explain amateurism.